The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1378/chest.10-3065
|View full text |Cite
|
Sign up to set email alerts
|

Statins and Brain Dysfunction

Abstract: Delirium is a manifestation of acute brain dysfunction that occurs in up to 80% of patients who are critically ill and is associated with higher mortality and long-term cognitive impairment (LTCI), which is akin to a dementia-like cognitive disability. [1][2][3][4][5][6][7] This acquired cognitive impairment-critical illness brain injury-has important public health implications for both younger and older patients (the latter an increasingly larger proportion of the population), threatening the functional indep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 55 publications
2
26
0
Order By: Relevance
“…Some experts have suggested that randomised trials of delirium should assess statins with both high and low lipophilic properties given the uncertainty about the effects on neuroinflammation. 8 However, both a lipophilic (ie, simvastatin) and non-lipophilic (ie, rosuvastatin) statin have been assessed in large randomised trials of patients with acute respiratory distress syndrome with similar findings of no beneficial effects on mortality and ventilator-free days. 23,61 Rosuvastatin was used in the SAILS trial on the basis of its superior bioavailability, risk of hepatic dysfunction, and drug–drug interactions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some experts have suggested that randomised trials of delirium should assess statins with both high and low lipophilic properties given the uncertainty about the effects on neuroinflammation. 8 However, both a lipophilic (ie, simvastatin) and non-lipophilic (ie, rosuvastatin) statin have been assessed in large randomised trials of patients with acute respiratory distress syndrome with similar findings of no beneficial effects on mortality and ventilator-free days. 23,61 Rosuvastatin was used in the SAILS trial on the basis of its superior bioavailability, risk of hepatic dysfunction, and drug–drug interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Data from both animal and human studies 58 offer indirect evidence that neuroinflammation, with associated oxidative damage and apoptosis, is an important part of the pathophysiology of delirium in the intensive care unit and subsequent long-term cognitive impairment. Severe sepsis is an archetype of systemic inflammation, including neuroinflammation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Statins have anti-inflammatory (9, 10), endothelial function-enhancing (11, 12), and anticoagulant effects (13, 14) that may interrupt the pathologic events thought to lead to delirium during critical illness. These pleiotropic effects make statins promising candidates for the treatment of delirium during critical illness (15) since they might interrupt the neuroinflammatory cascade hypothesized to contribute to delirium (16, 17). In addition, evidence suggests that treatment of acutely ill patients with statins can reduce inflammation (1820) whereas abrupt cessation of statins may cause rebound inflammation (21), leading to adverse cardiovascular outcomes (2225).…”
mentioning
confidence: 99%
“…65 A role for statins in both the treatment and the prevention of delirium in critically ill patients has been postulated. 125,126 With proinflammatory cytokines involved in the pathophysiology of delirium, future studies may examine the role of anti-inflammatory medications as adjuvant agents in combination with other medications.…”
Section: Resultsmentioning
confidence: 99%